Does The Digital Marketing Capability of Indonesian Banks Align with Digital Leadership and Technology Capabilities on Company Performance? - Banon Amelda; Firdaus Alamsjah; Elidjen Elidjen (CommIT (Communication and Information Technology) Journal, 2021)
Digital transformation is more than just providing online and mobile banking services. The banking and finance industry needs to innovate by combining digital technology with customer interactions. In this case, these new technology findings should make it easier and more convenient for users to access banking services. However, to understand the relationship between resources (capabilities) and performance, the empirical research is still very limited and rare to explain why some firms successfully use their capabilities while others do not. The aim of the research is to answer whether digital technology, digital leadership, and digital marketing have a significant influence on company performance. The research is a quantitative study using a survey method by distributing questionnaires to employees and leaders in banks. It obtains 100 respondents. The analytical method is the Structural Equation Model (SEM) approach using the Smart Partial Least Square (PLS) statistical software. There are several obtained results. First, digital technology capabilities have a positive and insignificant effect on company performance. Second, digital leadership capability significantly, positively affects digital technology capability and digital marketing capability. Third, digital marketing capability has a positive and significant effect on company performance. Finally, digital leadership capability only has a positive and significant effect on company performance after being mediated by digital marketing capabilities. However, the effect is not significant if it is mediated by digital technology capabilities.